A novel cognitive-behavioral stress management method for multiple sclerosis. A brief report of an observational study. (4th March 2019) - Anagnostouli, Maria; Babili, Ioanna; Chrousos, George; Artemiadis, Artemios; Darviri, Christina
ABSTRACT: Objectives : Psychological stress is an important risk factor for multiple sclerosis (MS) onset, relapse, neurological symptoms and psychosocial adjustment to the disease. Mounting evidence suggests that stress management could halt the disease progression and improve patients' wellbeing. The aim of this study was to investigate the effectiveness of a novel cognitive-behavioral stress management technique (called Pythagorean Self-Awareness Intervention – PSAI) routinely used in our clinics in patients with MS. Methods : In this observational study, 148 MS patients receiving PSAI for 8-weeks were compared patients who followed only usual care. Measurements included cognitive function, psychological distress and physical fatigue. Propensity score (PS) methods (given the observational design) and linear mixed models were employed to address study's endpoints. Results : A total of 128 (86.5%) of MS patients fulfilled the PS criteria for analyses (72 in the PSAI group and 56 in the control group). Patients of tertiary education, longer disease duration, higher cognitive score and psychological distress were more likely to choose to participate in the PSAI group. PSAI patients were found with statistical significant beneficial changes in cognitive speed processing, verbal memory, stress, anxiety, depression and fatigue. Based on the numbers-needed-to-treat of the weighted data, PSAI was particularly effective in improving cognitive speed processing (NNT = 10) and stress (NNT = 12). Discussion : PSAI can benefit cognitive function and psychological distress in MS patients. Future studies should expand these results in randomized trials and by using longer follow-up and MS activity-related endpoints. Abbreviations : BICAMS: Brief International Cognitive Assessment for Multiple Sclerosis BVMT-R: Brief Visuospatial Memory Test Revised CVLT: California Verbal Learning Test DASS: Depression Anxiety Stress Scale EDSS: Expanded Disability Status Scale MS: Multiple Sclerosis NNT: Numbers Needed to Treat PS: Propensity Score PSAI: Pythagorean Self-Awareness Intervention RR: Relapsing Remitting SDMT: Symbol Digits Modalities Test VAS-PF: Visual Analogue Scale Physical Fatigue